2002
DOI: 10.1074/jbc.m109466200
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of L-type Voltage-dependent Calcium Channels after Long Term Exposure to Nicotine in Cerebral Cortical Neurons

Abstract: Effects of long term (72-h

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 57 publications
2
54
0
1
Order By: Relevance
“…In addition, the up-regulation of L-type HVCC subunits similar to that observed in the cerebral cortex from animals with physical dependence on ethanol and nicotine occurs in neuronal cells continuously exposed to ethanol and nicotine as well as morphine (17,25,28,29). The previously reported observations and the present data obtained by the radiolabeled dihydropyridine binding assay and immunoblot analysis for L-type HVCC subunits indicate that the up- regulation of α1C and α1D of L-type HVCCs and the α2/ δ1 subunit play important roles in the development of physical dependence on morphine as well as ethanol and nicotine.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition, the up-regulation of L-type HVCC subunits similar to that observed in the cerebral cortex from animals with physical dependence on ethanol and nicotine occurs in neuronal cells continuously exposed to ethanol and nicotine as well as morphine (17,25,28,29). The previously reported observations and the present data obtained by the radiolabeled dihydropyridine binding assay and immunoblot analysis for L-type HVCC subunits indicate that the up- regulation of α1C and α1D of L-type HVCCs and the α2/ δ1 subunit play important roles in the development of physical dependence on morphine as well as ethanol and nicotine.…”
Section: Discussionmentioning
confidence: 77%
“…In the case of L-type HVCCs, the subunits to form Ca 2+ channels are divided into four isoforms, Ca v 1.1 (α1S), Ca v 1.2 (α1C), Ca v 1.3 (α1D), and Ca v 1.4 (α1F); and all of these subunits have dihydropyridine binding sites (12,13). α1C and α1D subunits are localized in neurons, and α1S and α1F subunits are dominantly present in skeletal muscles and retina, respectively (12, 13), although we reported the presence of the α1F subunit in mouse cerebral cortical neurons (17). Among these subunits of L-type HVCCs, α1C and α1D subunits are up-regulated in the cerebral cortex of animals physically dependent on ethanol and nicotine (10,18).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…] influx into neurons and the increase was completely abolished by L-type HVCC inhibitors (21). Moreover, long-term exposure to nicotine significantly increased the B max value with no changes in the K d value of [ 3 H]verapamil binding to the particulate fractions prepared from neurons exposed to nicotine, and this increase was significantly suppressed by mecamylamine (19).…”
Section: +mentioning
confidence: 80%
“…These data indicate the number of protein molecules composing L-type HVCCs. Western blot analysis on subunits consisting of L-type HVCCs revealed that the immunoreactivities against a 1 and a 2 / d 1 subunits of L-type HVCCs in neuronal membrane obtained from neurons exposed to nicotine were significantly higher than those from the non-treated neurons (21) (Fig. 2).…”
Section: +mentioning
confidence: 99%